Construction of EpCAM overexpression and knockdown vectors and their implications in colorectal cancer research - Wang, Bingping; Duan, Jinkai; Zhou, Jie; Ma, Hulin; Ren, Meng; Chen, Liangquan; Su, Rina; Zhang, Hao; Zhang, Shuang; Gao, Yanwei (Frontiers in Genome Editing, 2025)
BackgroundThe functional characterization of Epithelial Cell Adhesion Molecule (EpCAM) in colorectal cancer (CRC) progression has been constrained by methodological limitations, particularly the potential for truncated protein isoforms to confound traditional genetic knockout approaches. This study aimed to develop a novel CRISPR/Cas9 strategy to overcome this challenge and systematically elucidate the context-dependent oncogenic roles of EpCAM across diverse CRC models.MethodsWe engineered EpCAM overexpression (pCDH-EpCAM) and CRISPR/Cas9 knockdown (pGMC-KO-EpCAM) vectors using restriction digestion and T4 DNA ligation. A strategic dual-exon targeting approach (exons 1 and 3) was employed to minimize the risk of functional escape variants. Selected CRC cell lines (HT-29, HT-115, HRT-18) were genetically modified using optimized Lipofectamine 2000 transfection. Functional impacts were quantitatively assessed through: (i) flow cytometry for EpCAM surface expression (CD326-PE); (ii) daily cell counting over 8 days for proliferation kinetics; and (iii) scratch wound healing (0/24/48 h) and Transwell migration assays (8-μm pores, 18 h) to evaluate metastatic potential.ResultsSuccessful genetic modulation was achieved and validated: HT-29-OE-EpCAM-2 exhibited an 89% EpCAM-positive rate versus 12% in wild-type (WT) (*p*<0.001), while HRT-18-KD-EpCAM-3 showed a significant reduction to 4% EpCAM-positive cells (vs. 15% in WT, *p*<0.001). EpCAM overexpression accelerated proliferation, with HT-29-OE cells showing a 20.1% increase in peak density on day 5 (30.76 ± 0.15 × 104 vs. WT 25.62 ± 0.25 × 104; *p*<0.001). Conversely, EpCAM knockdown in HRT-18 cells prolonged the doubling time by 8.8% (30.8 h vs. WT 28.3 h; *p*<0.05). Migration capacity was profoundly altered: HT-115-OE cells achieved complete scratch closure (100% vs. 74.05% in WT, *p*<0.001), whereas HRT-18-KD cells showed an 80.5% reduction (*p*<0.001). Transwell migration hierarchy confirmed the pro-metastatic role of EpCAM (HT-29-OE > HT-115-OE > HRT-18-KD; ANOVA *p* = 0.0024).ConclusionThis study establishes a robust dual-vector toolkit for reliable EpCAM manipulation, highlighting a novel exon-targeting strategy that mitigates the limitations of previous approaches. Our findings demonstrate that EpCAM is a master regulator of CRC aggressiveness, dictating proliferative and metastatic phenotypes in a cell context-dependent manner. The genetically defined models provide a validated platform for therapeutic screening and safety assessment, forming a foundational resource for advancing EpCAM-targeted therapies and diagnostic applications.